Beyond the Last War: Balancing Ground Forces and Future Challenges Risk in USCENTCOM and USPACOM - Freier, Nathan; Sanok, Stephanie; Guy, Jacquelyn (Rowman & Littlefield Publishers, 2013)
There are currently real pressures on U.S. ground forces to define their contingency future. For example, there is a perceived decline in plausible conventional warfighting scenarios, and many see maintaining large standing ground capabilities solely as a hedge against uncertainty as cost-prohibitive in an era of declining resources. As U.S. officials will undoubtedly want to consider the widest possible range of military options in the event of future crises, this study endeavors to identify ground force options that are most important to the security of core U.S. interests in two key regions of the world: the Middle East and South Asia; and the Asia Pacific. It is meant to help the Department of Defense define future challenges risk as it relates to ground forces and identify and classify specific qualitative risks that could undermine future operational success. While the study focuses on U.S. Central Command (USCENTCOM) and U.S. Pacific Command (USPACOM), its findings are likely relevant worldwide.